KECANDUAN MENONTON DRAMA KOREA DAN PERILAKU IMITASI PADA SISWA SMA NEGERI 12 PEKANBARU - Rizka Yulia Putri; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The progress of the world of film is very interesting because it can make someone addicted like watching Korean drama. The pleasure of excessive Korean dramas to the point of addicts can lead to dependence and difficulty breaking away on matters relating to Korea, which can disrupt aspects of life. Therefore, the authors are interested to doing research with title "addicted to watching Korean dramas and imitation behavior on students of SMA Negeri 12 Pekanbaru". The purpose of this research is to know the description of addiction to watch Korean drama and to know the description of imitation behavior on students of SMA Negeri 12 Pekanbaru. This research is a descriptive method. To analysis the data using the percentage formula. This research uses purposive sampling technique with criterion of students who watch Korean drama 5-6 and >6 episode in one watch. The subject of this research is 48 students. The results of this study is 1) students who are addicted confused to choosing others activities or watching Korean dramas, excited feeling while watching Korean dramas, subject daily activities are watching Korean dramas, has the feeling of wanting to watching again the Korean drama after quitting, and anxiety if not watching Korean drama. 2) Behavior focus on students of SMA Negeri 12 Pekanbaru who is addicted to drama drama Korea in general are in low category. For more detail is speaking style in verbal and non-verbal, in a student-style dress that uses accessories, makeup, and fashion styles, and declare self is self-pose photo, attitudes, and Korean drama challenges. For students who are addicted to watching Korean dramas are expected to reduce the habit of watching Korean dramas, in order to use time to learn.Keywords : Addict, imitation behavior, Korean drama, watching.